Illustrations in a dictionary. Visual forms of entry presentation in a learner‘s dictionary - Kaczmarek, Hanna (Glottodidactica, 2016)
In this article we will subject visual forms of entry presentation found in monolingual learner's dictionaries to critical contrastive analysis. The characteristics of dictionaries under discussion, especially those addressed to foreign users, make them an essential language learning aid. The aim of the analysis is to identify which entries are effectively illustrated to constitute an effectual support of a verbal definition, and how it is achieved. The results of the analysis will indicate the possibilities and limits of illustrating concepts in dictionaries.